Komunikasi Sosial Pelaksanaan Pujawali Di Pura Linggasana Kelurahan Rembiga Kecamatan Selaparang Kota Mataram - Gede Ardana; I Nyoman Murba Widana; Ni Putu Sudewi Budhawati (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
This study aims to determine the phenomenon of social communication in the implementation of ceramics. Observation in the field, is how the form of social communication in the implementation of pujawali in Linggasana temple. The form of Hindu pujawali ceremonies in Kelurhan Rembiga includes: forms of social communication, social communication relations and social communication strategies between Muslims running in harmony. Conducting forms of social communication is the most important part of all activities, so that understanding arises in completing the tasks of each pawawali. Basiccally the communication made by Hindus is not only in the form of notifying and listening alone. But the form of communication must contain the sharing of ideas, thoughts, facts or opinions. Communication consists of six types, and one of them is two-way communication, can be face-to-face, can be feedback, overcome problems from other parties, speed to reach targets, interpersonal. This type of research is descriptive qualitative with a phenomenological approach. Data collection techniques through observation, interviews, and documents, this study uses data analysis and checking the validity of the data to determine the validity of a study. The theory used is structural functional theory, social exchange theory, interactionalism theory. The findings in this study there are 3 points, namely: a form of communication, awareness and good reception from all people in Rembiga about the implementation of pujawali. Communicating in the form of social communication is the most important part of all activities when pujawali internal and external relations to social communication itself, is a relationship that must be nurtured and become harmonious fertilizer originating from within individuals related to the physical and psychological conditions of Hindu and Muslim communities. Strategies of social communication in the implementation of pawawali: A well-planned communication strategy before starting ceremonial activities are steps or stages that must be carried out by, measured and directed in order to achieve safe implementation. The meaning of social communication in the implementation of Hindu religious ceremonies in the city of Mataram includes: religious meaning, social meaning, social meaning, the meaning of unity.